1995
DOI: 10.1111/j.2042-7158.1995.tb05856.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in Electrically-induced Responses of Rat Seminal Vesicles

Abstract: Contractile responses of rat isolated seminal vesicle were elicited by electrical field stimulation (EFS, 10 Hz, 1 ms, 40 V for 5 s), noradrenaline (1 x 10(-5) M) and carbachol (1 x 10(-5) M). Guanethidine (2 x 10(-5)-5 x 10(-4) M) progressively reduced the contraction induced by EFS and carbachol to 24 +/- 2 and 10 +/- 2%, respectively, at the highest concentration (n = 6), while potentiating noradrenaline contraction to a maximum of 154 +/- 14% at 2 x 10(-5) M (n = 6). Prazosin (1 x 10(-6) M) and atropine (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…In addition to the retrograde inflow attributable to insufficient closure of the bladder neck, insufficient contraction of the seminal vesicles may also occur under silodosin administration. It has already been reported that α 1A receptors are present in the spermatic ducts and seminal vesicles 13–15 . The findings of the present study are consistent with the report that contraction of the seminal vesicles is involved in ejaculation.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to the retrograde inflow attributable to insufficient closure of the bladder neck, insufficient contraction of the seminal vesicles may also occur under silodosin administration. It has already been reported that α 1A receptors are present in the spermatic ducts and seminal vesicles 13–15 . The findings of the present study are consistent with the report that contraction of the seminal vesicles is involved in ejaculation.…”
Section: Discussionsupporting
confidence: 94%
“…There were no treatment-related histopathological changes of the seminal vesicle, indicating that atropine itself did not affect the secretion of seminal vesicle fluid. Therefore, the increased seminal vesicle weights and decreased copulatory plug weights in the atropine group were considered to be resulted from inhibition of contraction of the seminal vesicle during the process of emission, which is one of the pharmacological effects of the muscarinic receptor antagonists (Sadraei et al, 1995). It has been reported (Gokhale et al, 1996) that contractile responses of rat isolated seminal vesicles induced by electrical field stimulation involve participation of a noradrenergic as well as a cholinergic mechanism, which also supports the results of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…3,9,[21][22][23] Also, the frequency-dependent contractions of SV, elicited by the EFS, have been reproduced in a few experiments, which occur through neurotransmitters including acetylcholine and adenosine triphosphate. 10,[24][25][26] The results of this study showed that the proportion of tissues responding to the drugs and EFS was greater for the rings than the strips. When evaluating the methodological efficacy, we focused not on the absolute response magnitude in a responding tissue but the response rate.…”
Section: Discussionmentioning
confidence: 99%